Carbon trading-based layered operation optimization of the electric–thermal multi-energy-flow coupling system with photothermal power stations - Hu, Changbin; Cai, Xiaoqin; Zhao, Xinyu; Luo, Shanna; Lu, Heng; Li, Xuecheng (Frontiers in Energy Research, 2023)
With the increasing development of the low-carbon economy, the coupling degree of electric heat and gas system is deepening, and the traditional energy supply system adopts the electric heat separation method, and the operation mode of hierarchical scheduling of transmission and distribution network has been difficult to tap into the resources of the whole network and realize the globally optimal operation strategy. To improve the new energy consumption, and at the same time solve the multi-energy flow coupling system, this paper proposes a layered optimization operation strategy for the electric-thermal multi-energy flow coupling system under the carbon trading mechanism of the Concentrated solar power(CSP) power plant and carbon trading mechanism. The upper layer is the multi-energy flow coupled system solving layer, and the Newton method, improved Newton method and improved second-order cone solving method are proposed for solving the matrix value of the complex multi-energy flow coupled system; the lower layer is the multi-energy flow optimization solving layer, and based on the solving value of the system obtained from the upper layer, the optimization of the lower layer is based on the goal of minimizing the total cost of the user economy, and the model of the carbon trading mechanism is introduced for the optimization of the time-sequence output of electrical and thermal units in different scenarios, and the solution is based on the mixed-integer linear method. The mixed-integer linear programming method is used. Finally, the effectiveness is verified by simulation examples. The results show that this strategy improves the economy in facing the other four perspectives by12.7%, 131.9%, 29.6%, and10.14%, respectively.; in demand response, it reduces the unfavorable factors of setting heat by electricity as well as heat by electricity, enhances the economic feasibility of the system, and ensures the reliability of the system's energy supply; the operation rate reaches0.11s, and the precision reaches1e-3, which improves the system's accuracy and rapidity.